Paradigma Kritis Pancasila Dalam Dimensi Pendidikan Islam - Astuti, Mardiah; Herlina, Herlina; Ibrahim, Ibrahim; Juliana, Rina; Pardika, Rinto; Imelda, Ovi (Faidatuna, 2023)
In today's modernization era, it is very important for an institution to combine the values of Pancasila and the dimensions of Islamic education. Through this article we can find out the form of the critical paradigm of Pancasila and the factors that influence the crisis of Pancasila in the dimension of Islamic education and provide solutions to problems that may arise. This research method uses qualitative descriptive methods with a descriptive approach. Research informants consisted of three responders, namely students of Raden Fatah State Islamic University Palembang, the community around campus A UIN Raden Fatah Palembang, and finally students of other universities. Data were collected through observation and direct interviews. Data analysis is collected through qualitative descriptive, so that deep and accurate conclusions are obtained on the problems studied. The results of this study are first, That is the form or form of the Pancasila crisis paradigm which can be described as the Pancasila philosophy. Describe it as the philosophy of pancasila itself. Second, the factors that influence the critical paradigm of pancasila in the dimension of Islamic education are 1) The theme of evic educational democracy, 2) Multicultural culture, 3) Economy, 4) Mindset, 5) Pancasila values, 6) Education, 7) Social, and 8) Educational environment. Finally, the solution to maintain the sovereignty of the critical paradigm of Pancasila in the dimension of Islamic education, among others: improving the quality of efficiency of Islamic education, cultural approaches, internalizing education, implementing behaviors contained in the values of Pancasila.